In vitro test to evaluate survival in the gastrointestinal tract of commercial probiotics - Maritiele Naissinger da Silva; Bruna Lago Tagliapietra; Vinícius do Amaral Flores; Neila Silvia Pereira dos Santos Richards (Current Research in Food Science, 2021)
The search for functional foods grows constantly, and in this demand, the supply of industries that seek to produce and sell supplements also grows, as is the case of probiotics freely sold in pharmacies and supermarkets. Given a large number of foods with probiotic appeal and supplements sold without the need for a nutritional or medical prescription, this study came up to evaluate the viability of commercial probiotic cells, through in vitro gastrointestinal simulation and analyzing the information present in their labeling. Eleven commercial probiotic samples were analyzed, and viable cell counts were performed before and after in vitro simulation. These products usually use appealing labeling and induce the consumer to purchase these probiotics, which often do not offer the benefits described on the packaging. The results showed that only two samples had the initial concentration indicated on their labeling and four samples offered a concentration of 3 log CFU g−1 in the ileum portion. All samples had a reduction in concentration during the gastrointestinal simulation, which varied from 1 to 4 log CFU g−1, but most do not fulfill the offer of a probiotic supplement, and there should be more inspection and control over the commercialization of this product niche.